Respuesta :

Answer:

27

36

Step-by-step explanation:

So if they are consecutive multiples of 9, just make the numbers you multiply by x and x + 1

9x + 9x + 9 = 63

18x = 54

x = 3

3 * 9 = 27

4 * 9 = 36

CHECK:

27 + 36 = 63

snog

Answer:

see below

Step-by-step explanation:

We can write the first number as 9n because it is a multiple of 9, and the second number will be 9(n + 1). We can write:

9n + 9(n + 1) = 63 because they have a sum of 63.

9n + 9n + 9 = 63

18n + 9 = 63

18n = 54

n = 3

This means that the first number is 9 * 3 = 27 and the second is 9 * (3 + 1) = 9 * 4 = 36.